Comparison of early non-pharmacological interventions in COVID-19 mortality from Peru and the United States of America: Comparación de las intervenciones no farmacológicas tempranas en la mortalidad por COVID-19 de Perú y Estados Unidos de América - Grillo-Rojas, Pedro Fidel (2020)
Introduction: The pandemic that has been developing at a global level has tested not only the differenthealth systems of the world, but also the economic models and governments in each of the countries.Objective: To compare the non-pharmacological interventions of early application in the displacementand the amplitude of the daily mortality curve per million; as well as calculating the accumulatedmortality rates and the number of deaths avoided by CORONAVIRUS SARS-Cov2 between Peru and theUnited States. Methods: The daily mortality rate per million from the first registration, the maximumpeak and the amplitude of said rate were evaluated, as well as the accumulated rate for both countrieswas calculated and evaluated under the difference in differences method, to estimate the death rateavoided per million. Results: Mortality per million in Peru was 0.061 and in the United States 0.069.The first peak day in Peru recorded mortality in the order of 3.276 per million inhabitants at 46 days,and in the US it was 14.88 per million at 47 days. The difference in differences is equivalent to a rate of-164,193 deaths per million, in Peru with respect to the United States of America. Conclusion: The earlyimplementation of non-pharmacological interventions including quarantine is related to a lower dailymortality and accumulated mortality rates per million in Peru compared to the United States of America.